Self-management in professional orientation for young athletes - Gretsov, A. G. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to reveal the scientifically approved psychological and pedagogical technology for young athletes to manage their professional expectations by themselves for the successful furthermore professional self-determination.